Impact of Rapidly Deployed COVID-19 Monoclonal Antibody Infusion Clinics on Rate of Hospitalization. Issue 2 (March 2022) - Delasobera, Bronson E.; Saggar, Tara; Goodwin, Jennifer N.; Joy, Amanda; Henry, Kiersten N.; Levin, Bonnie; Hager, David D.; McAlduff, Joel; DeSale, Sameer; Owens, Xavier; Wortmann, Glenn W.; Kumar, Princy N.
Abstract : Background: Providing monoclonal antibody therapy infusions requires challenging logistics, resources, and technology, hindering availability across the United States. Early identification and treatment of COVID-positive patients can reduce hospitalizations. Objective: This study aimed to describe the referral, selection process, and deployment of outpatient monoclonal infusion clinics, as well as the impact of monoclonal antibody therapy in COVID-positive patients on the rate of emergency department (ED) visits and hospitalization. Methods: This is a retrospective cohort study that used screening of all COVID-positive ambulatory patients using a unique scoring rubric embedded in the emergency medical response for appropriateness for therapy between November 2020 and January 2021. Participants included all outpatients testing positive for COVID-19 were screened, and those eligible were referred for treatment with bamlanivimab. Of the 443 patients referred for treatment, 252 patients were treated with bamlanivimab compared with 191 patients who declined treatment. Patients were treated either in 1 of the 2 outpatient infusion centers (74%) or the ED (26%.) Results: Of 443 patients with positive COVID-19 diagnoses who were eligible for treatment based on a risk assessment rubric, 252 received bamlanivimab. There was a significant reduction in hospitalization of the treatment versus control group (6.7% vs 13.6%, P < 0.05). No significant differences were noted in risk score at screening, ED visits after infusion, days of symptom onset at screening or infusion, or death. Conclusions and Relevance: The efficacy of monoclonal antibody therapy on reducing hospitalization was demonstrated. Rapid development of screening technology, scheduling and operational logistics, and physical space can overcome the challenges in the current environment.